Alunos bolsistas em uma escola particular: um estudo sobre a dimensão subjetiva da desigualdade social - Salvatico, Bianca Mendes (2015)
This dissertation aims to understand the subjective senses maded by scholarship students of basic education in a private school in São Paulo. The justification is based on the assumption that when we study the scholarship student in private schools, we have the possibility to investigate the subjective dimension of social inequality, based on the idea that this social phenomenon is not constituted only by an objective dimension, but also by ways of acting, feeling and living that makes a subjective framework that is rarely considered as a formative aspect of the subject. The theoretical framework chosen is the Socio-Historical Psychology, whose conceives man an active, historical and social human in a continuous transformation process, based ond theories of Rey (2005) and Aguiar and Ozella (2006). The data emerging from research conducted by collective interviews focusing on seven scholarship students experience in a private school. The analysis is done by the construction of meanings cores who expressing the central points of the subject and what is emotionally involved. The results indicate understanding of that relationship and how the whole experience of scholarship students is constructed. We intend to contribute to the knowledge of the area of research in social inequality, to reveal the subjective senses of the subjects participating in the school process, to understand them in their entireties, which may open new perspectives of the various manifestations of social inequality in brazilian society